2019
DOI: 10.1159/000503069
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Season of Birth on Psychiatric Disorder Susceptibility and Drug Abuse Incidence in a Population from the Köppen Tropical Savanna Region of Brazil

Abstract: <b><i>Background:</i></b> Despite much evidence that season of birth (SOB) my influence the vulnerability to psychiatric disorders, divergence has been reported, in particular between populations born in the northern and southern hemispheres. We analyzed the potential modified risk by SOB to psychiatric disorder or drug addiction comorbidity in a population born in the Triângulo Mineiro region, a southern hemisphere Köppen tropical savanna region in Brazil. <b><i>Method:<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients 1,3,5,6,27‐73 . The meta‐analytic results of our findings and included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients 1,3,5,6,27‐73 . The meta‐analytic results of our findings and included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients. 1 , 3 , 5 , 6 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , …”
Section: Resultsmentioning
confidence: 99%
“…A hemispheric six-month shift has also been observed between seasonality and depression symptoms, with higher scores associating with spring births (March-May) in the Northern hemisphere and autumn births (September-November) in the Southern hemisphere, in a small young adult and adolescent cohort [ 61 ]. Although an excess of August births in MDD patients has also been observed in the Southern hemisphere within a Brazilian retrospective study of MDD cases and controls ( n = 98,457) [ 62 ]. However, no associations between month of birth and depression symptoms were found in a similarly aged cohort in a recent Europe wide study ( n = 72,370) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that early light exposure could be beneficial for developing an internal clock that has flexibility to adapt to external circadian challenges [ 136 ] that could partially help explain some reports on the impact of season of birth on psychiatric disorders. Thus, light does not only serve as the major seasonal challenge but also has an impact on our ability to adapt to light changes [ 137 ]. Further, with globalization, more and more people start living far away from where they were born.…”
Section: Individual Variationsmentioning
confidence: 99%